Associations between illness beliefs, medication beliefs, anticoagulation‐related quality of life, and INR control: Insights from the Switching Study. Issue 3 (7th June 2018) - Bartoli‐Abdou, John K.; Patel, Jignesh P.; Xie, Rosa; Dzahini, Olubanke; Vadher, Bipin; Brown, Alison; Roberts, Lara N.; Patel, Raj K.; Arya, Roopen; Auyeung, Vivian
Abstract: Background: Anticoagulation control with vitamin‐K antagonists (VKAs) in patients with atrial fibrillation (AF) or venous thromboembolism (VTE) can be measured using time in therapeutic range (TTR), where TTR >65% is considered good and low TTR may be associated with low adherence. Methods: This cross‐sectional observational study compared illness beliefs, treatment beliefs, and treatment satisfaction of patients with TTR >75% and TTR <50% using validated tools to determine their association with TTR. Adults requiring chronic VKA therapy were recruited from 2 hospital anticoagulation clinics in London, UK. Results: 311 patients with TTR >75% and 214 with TTR <50% were recruited. TTR >75% patients had been taking warfarin on average over 2 years longer than TTR <50% patients ( P  <   .001). Statistically significant differences in beliefs were found in all subscales other than in treatment control, general harm, and general overuse. Cluster analysis determined there were 4 distinct clusters of beliefs among patients. Multivariate binary logistic regression found VTE patients were least likely to have poor TTR (OR = 0.49; 95% CI 0.29, 0.77). Patients in the "cautious of therapy and fearful of illness" cluster were most likely to have low TTR (OR = 4.75; 95% CI 2.75, 8.77). Conclusion: Illness perceptions, medication beliefs and treatment satisfaction were associated with INR control. VTE patients and those who were accepting of both illness and treatment were most likely to have optimal INR control.